Immunohistochemical localization of tissue factor pathway inhibitor-2 in human tumor tissue - Wojtukiewicz, Marek Z.; Sierko, Ewa; Zimnoch, Lech; Kozlowski, Leszek; Kisiel, Walter (Thrombosis and Haemostasis, 2003)
The progression of neoplasms is frequently associated with thromboembolic complications. Coagulation proteins, particularly tissue factor (TF), have been shown to play a role in tumor growth and metastatic dissemination. TFPI is the principal inhibitor of TF-dependent pathway of blood coagulation, but previous studies failed to detect antigenic TFPI in cancer tissue. Recently, a second inhibitor of tissue factor dependent pathway, TFPI-2 (also known as placental protein 5 [PP5] or matrix-associated serine protease inhibitor [MSPI]), has been described. Information on the presence of TFPI-2 within the malignant tumor tissue still remains obscure, and thus the aim of this study was to evaluate the expression of TFPI-2 in loco in several different neoplasms. TFPI-2 expression was demonstrated by immu-nohistochemical procedures in neoplastic cells of laryngeal, breast, gastric, colon, pancreatic, renal and endometrial cancer, as well as glial neoplasms. The intensity of staining was not uniform, with higher intensity in more differentiated tumors. G3 breast, gastric, endometrial and colon cancer cells revealed populations of cells that were either TFPI-2 positive or negative. Gastric and renal cancer tissue exhibited the presence of TFPI-2 in tumor infiltrating macrophages. TFPI-2 was also observed in normal tissue of the breast, stomach, colon and pancreas. These data demonstrate that the expression of TFPI-2 diminishes with an increasing degree of malignancy, which may suggest a role for TFPI-2 in the maintenance of tumor stability and inhibition of the growth of neoplasms.
Keywords: Tissue factor pathway inhibitor-2; tumor tissue; immunohisto-chemistry